Biopsy and the diagnostic evaluation of musculoskeletal tumours: critical but often missed in the 21st century. Issue 3 (2nd August 2015) - Trieu, Jason; Sinnathamby, Mathuranthakan; Di Bella, Claudia; Pianta, Marcus; Perera, Warren; Slavin, John L.; Schlicht, Stephen M.; Choong, Peter F. M.
Abstract: Bone and soft‐tissue sarcomas are rare and heterogeneous malignancies arising from tissues of mesenchymal origin. Treatment planning is informed by accurate diagnosis for which biopsy is the diagnostic standard. Biopsy in the setting of suspected malignancy is a technically challenging procedure that should only be performed at specialist institutions. Without the requisite expertise, they can compromise the viability of reconstructive procedures and may make necessary amputation to achieve adequate surgical margins. The risk of complications arising from the procedure must be minimized and therefore biopsy should always be preceded by imaging. There must be no attempt at biopsy or excision prior to referral if there is any suspicion of malignancy. Patients with suspected bone and soft‐tissue tumours are best evaluated and treated at specialist sarcoma centres under the care of expert multidisciplinary teams. Prompt referral to a specialist sarcoma centre should always be made prior to biopsy for any suspicious mass that is painful, progressively increasing in size, greater than 5 cm in diameter, deep to deep fascia or recurs following inadvertent excision.